Uncovering the oxic-suboxic microenvironment change in seamount flank through authigenic clay minerals in basaltic substrate of ferromanganese crust, Magellan seamount - An, Hyeonho; Jung, Jaewoo; Hwang, Huijeong; Kim, Suhyun; Kim, Jonguk; Ko, Youngtak; Yang, Kiho (Frontiers in Marine Science, 2024)
In low-temperature ocean environments, basalt alteration by seawater precipitates authigenic clay minerals that serve as proxies for reconstructing paleo-ocean conditions because they reflect surrounding oxic-suboxic conditions. In this study, alteration rims on basaltic substrate associated with ferromanganese (Fe-Mn) crust from the Magellan seamount KC-7 were identified by microscopic analyses. Mineralogical and geochemical analyses indicate that the alteration rims contain K-enriched Fe-smectite and glauconite which suggest that seawater-basalt interaction occurred under oxic conditions and in the presence of organic-rich suboxic conditions, respectively. These disparate environmental conditions suggest that the environment changed before and after Fe-Mn crusts formed. During the Cenozoic hyperthermal events, oxygen-rich bottom water was supplied by upwelling driven by the geomorphological influence of the seamounts, which may have led to basalt alteration. The K-enriched Fe-smectites, which indicate oxic condition, formed via seawater-basalt interactions before the Fe-Mn crust incrustation. Later, during the Eocene, the opening of the Drake Passage enhanced the supply of oxygen-rich seawater to the Magellan Seamounts, thereby enabling the formation of hydrogenetic Fe-Mn crust. After the incrustation of seamount flanks with Fe-Mn crusts, the carbonate fluorapatite (CFA), a product of the global phosphatization event, filled the pores in the Fe-Mn crusts during Oi-1 glaciation. As a result, seawater-basalt interactions decreased and led to suboxic conditions, in which glauconite formed as organic matter was remineralized under the organic-rich conditions in the basaltic substrate. This authigenic clay mineral formation sequence suggests that changes in ocean circulation and subsequent changes in the oxic-suboxic conditions in the basaltic substrate occurred on the western Pacific seamount KC-7.